2001
DOI: 10.1172/jci13930
|View full text |Cite
|
Sign up to set email alerts
|

Histamine regulates cytokine production in maturing dendritic cells, resulting in altered T cell polarization

Abstract: Atopic diseases such as allergy and asthma are characterized by increases in Th2 cells and serum IgE antibodies. The binding of allergens to IgE on mast cells triggers the release of several mediators, of which histamine is the most prevalent. Here we show that histamine, together with a maturation signal, acts directly upon immature dendritic cells (iDCs), profoundly altering their T cell polarizing capacity. We demonstrate that iDCs express two active histamine receptors, H1 and H2. Histamine did not signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
235
0
6

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(260 citation statements)
references
References 53 publications
(18 reference statements)
19
235
0
6
Order By: Relevance
“…IL-12p70 suppression via the H2R observed in our study is in agreement with previous studies (10,12,13). The ability of the G␣ s -coupled H2R to induce cAMP in monocytes and MoDC has been described previously (11,12,35,36).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…IL-12p70 suppression via the H2R observed in our study is in agreement with previous studies (10,12,13). The ability of the G␣ s -coupled H2R to induce cAMP in monocytes and MoDC has been described previously (11,12,35,36).…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies were controversial at this point; Idzko et al (12) found a suppression of IL-12p70 production by R-␣-MeH, whereas Mazzoni et al (13) and Caron et al (10) were unable to reduce histamine-induced IL-12p70 production with the H3R and (less efficient) H4R antagonist thioperamide. In our experiments, histamine-induced IL12p70 suppression was rescued by thioperamide pretreatment of MoDC (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…12,13 As activators of cytokine production in response to infection, TLRs may participate in early life Th1 immunophenotype development. 14,15 Genetic variation in these receptors may thus influence risk for either Th1 (infectious) or Th2 (atopic) disease. Additionally, two missense mutations of the TLR4 gene (Asp299Gly and Thr399Ile) have been associated with a decreased response to inhaled endotoxin in humans.…”
Section: Resultsmentioning
confidence: 99%